Cover Image. (12th May 2022) - Kurita, Yuko; Kanno, Satomi; Sugita, Ryohei; Hirose, Atsushi; Ohnishi, Miwa; Tezuka, Ayumi; Deguchi, Ayumi; Ishizaki, Kimitsune; Fukaki, Hidehiro; Baba, Kei'ichi; Nagano, Atsushi J.; Tanoi, Keitaro; et al.
Abstract : The front cover image is based on the Original Article Visualization of phosphorus re‐translocation and phosphate transporter expression profiles in a shortened annual cycle system of poplar by Yuko Kurita et al., https://doi.org/10.1111/pce.14319 .